English phonetics and phonology a practical course - Roach, Peter (Delhi Cambridge University Press, 2016)
Bridging the gap between simple pronunciation handbooks and technical phonetics and phonology textbooks, this new edition takes into account recent developments in the teaching of phonology.
Keywords: GEN